Face validity of a synthetic papilla designed for biliary sphincterotomy training - van der Wiel, Sophia E.; Koch, Arjun D.; Bruno, Marco J. (Endoscopy International Open, 2019)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is considered one of the most technically demanding endoscopic procedures. Still, limited data are available on simulators in ERCP training. Recently, the Boškoski-Costamagna ERCP Trainer was validated as a realistic training model by our study group. As an extension to this model, a novel synthetic papilla has been designed allowing to train biliary sphincterotomy. We aimed to determine the face validity of this synthetic papilla and its didactic value for training sphincterotomy.Methods Expert participants, each with more a than 2500 ERCPs lifetime experience, were invited to perform a biliary sphincterotomy and fill out a questionnaire on the realism of the procedure and the didactic value.Results A total of 40 ERCP experts were included, originating from 16 different countries. Experts’ opinion on realism of performing a biliary sphincterotomy was rated with a median of 7 on a 10-point Likert scale, resemblance of the performed maneuvers 8 and tactile feedback 7. When asked if the cutting was perceived as realistic, experts rated a 6 and the cutting result was rated 8. The potential of the cutting papilla as a training tool for novices was rated 4 on a 4-point scale and there was a high agreement among the experts to include the papilla in the training of novices (rating 4).Conclusion This is the first synthetic papilla available for training sphincterotomy on the Boškoski-Costamagna ERCP Trainer and it demonstrates good face validity. ERCP experts highly agree on its didactic value and added value in the training curriculum of novice endoscopists.